Using the mental visualization technique and deep breathing to develop the performance of the transmitter skill in volleyball Experimental research on some Baghdad youth volleyball clubs (Journal of the College of Basic Education, 2023)
Introducing the search:It includes the introduction, the importance of the research, and a problem that crystallized in the lack of use of modern psychological techniques represented by (mental visualization and deep breathing) within the physical and skill exercises because of their great importance in developing the level of performance of various skills.A delegation that included research objectives:To identify the level of performance of the serving skill for some Baghdad youth clubs in volleyball, to prepare and apply relaxation psychological techniques exercises (mental visualization, deep breathing), and then to identify the effect of relaxation techniques exercises on developing attention focus during the performance of the serving skill for youth volleyball players,